The war on human trafficking: U.S. policy assessed - DeStefano, Anthony M. (Rutgers University Press, 2007)
Introduction -- The barrio girls -- The emerging issue of trafficking -- The global response -- "We need this bill" -- The learning curve -- The orphan lady from pitesti -- Finding leku -- Sweat, toil and tears -- Sexual slavery -- New initiatives-more controversy -- The bully pulpit -- Assessment -- Final thoughts